Female job satisfaction: can we explain the part-time puzzle? - Bridges, Sarah; Owens, Trudy (Oxford University Press, 2017)
Although it is generally accepted that women who work part-time are, on average, more satisfied in their jobs than their full-time counterparts, this is unlikely to be true for all women. Using the British Household Panel Survey we estimate the determinants of job satisfaction using a fixed-effects linear regression and define categories of women according to their level of education, age-cohort, family circumstances, and pathway into part-time work. We show that women who work part-time are more satisfied with their jobs, although the effect is noticeably weaker for key groups: those born in or after 1970, the better educated, and those who enter part-time employment direct from full-time work. We argue that these results reflect shifting attitudes by women towards their employment. Women today, especially those belonging to the younger cohort expect more from their jobs and are beginning to express dissatisfaction if this is not realised.